Pembelajaran Pendidikan Agama Hindu Dan Budi Pekerti Dengan Kurikulum 2013 Di SD Negeri 1 Karangasem - I Ketut Sandiyasa; Dewa Komang Tantra; Ida Ayu Tary Puspa (Jurnal Penelitian Agama Hindu, 2019)
The purpose of this study was to find out (1) learning planning of Hindu Religion and Character Education with the 2013 Curriculum in Public Elementary School 1 Karangasem (2) Implementation of learning on Hinduism and Character Education with the 2013 Curriculum in Public Elementary School 1 Karangasem (3) Constraints related to learning process on Hinduism and Character Education at Public Elementary. The subjects of this study are Hindu teachers and Character teacher. The technique of determining the informants used is purposive sampling. The method used to collect data is the observation method, in-depth interview method, and document study method. Data are analyzed by using descriptive qualitative analysis method with steps of reduction, data presentation, conclusion, verification and final conclusions. The presentation of the results of data analysis was done informally in the form of narratives and formally in the form of tables, charts, and photographs. All research results are included in five chapters. The results of the study show (1) The learning plan of Hinduism and Character Education Alt The 2013 Curriculum implemented Ni Public Elementary School 1Karangasem has been good in accordance with the Regulation of Ministry of Education and Culture No. 22 of 2016 concerning process standards. Because of the 11 components examined, the problems found only in one component, namely the suitability of indicators with assessment instruments. (2) The implementation of learning Hinduism and Character Education with the 2013 Curriculum in Public Elementary Scool 1 Karangasem has been running well because of the 9 components observed only two components that are problematic namely the apperception activities and the closing of the lesson (3) The constraints in the learning planning of Hinduism and Character Education in Public Elementary School 1 Karangasem are related to the preparation of HOTS ( Higher Order Thinking Skils) questions, compilation of research instruments, making learning syntax, with co-positive models learning. Constraints on learning are dominant in the assessment of student discussions, the delivery of material that is still abstract and displays a skill related to basic competiion and invites students to make reflexes and learning conclusions..